Effect of Multiwalled Carbon Nanotubes on the Mechanical Properties of Carbon Fiber-Reinforced Polyamide-6/Polypropylene Composites for Lightweight Automotive Parts - Nguyen-Tran, Huu-Duc (Materials (Basel), 2018)
The development of lightweight automotive parts is an important issue for improving the efficiency of vehicles. Polymer composites have been widely applied to reduce weight and improve mechanical properties by mixing polymers with carbon fibers, glass fibers, and carbon nanotubes. Polypropylene (PP) has been added to carbon fiber-reinforced nylon-6 (CF/PA6) composite to achieve further weight reduction and water resistance. However, the mechanical properties were reduced by the addition of PP. In this research, multiwalled carbon nanotubes (CNTs) were added to compensate for the reduced mechanical properties experienced when adding PP. Tensile testing and bending tests were carried out to evaluate the mechanical properties. A small amount of CNTs improved the mechanical properties of carbon fiber-reinforced PA6/PP composites. For example, the density of CF/PA6 was reduced from 1.214 to 1.131 g/cm(3) (6.8%) by adding 30 wt % PP, and the tensile strength of 30 wt % PP composite was improved from 168 to 173 MPa (3.0%) by adding 0.5 wt % CNTs with small increase of density (1.135 g/cm(3)). The developed composite will be widely used for lightweight automotive parts with improved mechanical properties.